Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Hyaluronic acid and polyvinyl alcohol-based radioresponsive hydrogel for combined radioimmunotherapy of breast cancer bone metastasis - Liubing Li; Zenghui Gu; Yanxian Wu; Subin Lin; Xiaju Cheng; Leshuai W. Zhang; Jianzhong Qin; Qirong Dong; Yong Wang; Yangyun Wang (Carbohydrate Polymers, 2025)

A sudden drop in temperature causes an imbalance in skin mucus barrier homeostasis in grass carp (Ctenopharyngodon idella) - Yali Wang; Xiaoning Gao; Zihao Cheng; Rong Chen; Yangyang Zhang; Subin Cui; Siyu Zhang; Kun Hu; Congdi Wu (Aquaculture, 2025)

Occurrence, removal, and ecological risk of antibiotics and antibiotic resistance genes in township wastewater treatment plants in the upper reaches of the Yangtze River, China - Subin Cheng; Rutao Zhang; Qixuan Liu; Shangwei He; Jie Sun; Liqun Xing (Environmental Science and Pollution Research, 2024)

The Responses of Storm Surges to Representative Typhoons under Wave–Current Interaction in the Yangtze River Estuary - Jie Wang; Cuiping Kuang; Subin Cheng; Daidu Fan; Kuo Chen; Jilong Chen (Journal of Marine Science and Engineering, 2024)
Storm surge is one of the most remarkable natural calamities, which is shown as the abnormal sea level changes in the coastal waters during a typhoon event. To investigate the responses of storm surges to the typhoon paths, intensities and coastal dynamics, a coupled wave–current model is used to study the impacts of strong winds, considerable waves and complex currents on storm surges in the Yangtze River Estuary (YRE) during three representative typhoons of Fongwong (2014), Ampil (2018) and Lekima (2019) with different intensities and paths. The model is verified using the measured data on significant wave height and period, water level and current velocity and performs well in modeling real conditions. The numerical results demonstrate that (1) the maximum storm surge occurred in the South Channel (SC) during Fongwong and Lekima while in the North Branch (NB) during Ampil due to the typhoon path and the estuarine terrain. Among the three typhoons, Lekima presented the highest surge, with a maximum value of 1.17 m at SC2 (the inner point of the SC). There was a negative surge during Ampil, which reached −0.42 m at SC2, due to the representative path (SE to NW) and offshore wind action. (2) Tide is the main influencing factor of storm surge as the maximum or minimum value always occurs at the low or high tidal level, respectively. Meanwhile, typhoon intensity is important as it influences the variation rate of surge with higher intensity leading to a sudden increase in surge while the tidal intensity primarily affects the peak value. (3) The wave setup can counteract the wind-induced negative surge. The peak differences between storm surge isoline and wave setup isoline are 0.15, 0.2 and 0.2 m during Fongwong, Ampil and Lekima, respectively, which illustrates the impacts of the combined actions of the typhoon path and intensity on the wave setup. This research emphasizes the influences of wave–current interaction on estuarine storm surge during typhoon events and reveals the potential risks for oceanic disasters like coastal inundation.